PELATIHAN DAN PRAKTEK PEMBUATAN SABUN CUCI TANGAN CAIR DI PKK TEMBALANG PESONA ASRI - Kusumayanti, Heny; Paramita, Vita; Wahyunimgsih, Wahyunimgsih; Amalia, Rizka; Siregar, Vynda Dindasari; Pudiastuningtyas, Nurul (Vocational School Diponegoro University, 2018)
Heny Kusumayanti, Vita Paramita, Wahyunimgsih, RizkaAmalia, Vynda Dindasari Siregar, Nurul Pudiastuningtyas, in this paper explain that soap is used as a cleaning agent. Hand sanitizer is a hand sanitizer which makes it easy and can be carried out by PKK mothers and the community. The purpose of this liquid handwashing soap training and practice is to provide knowledge and appropriate technology to the PKK mothers in Tembalang Pesona Asri RT I RW IV Kramas Semarang, in addition to making their own liquid handwashing for self consumption can also be sold so can increase income. The result of this activity is liquid hand washing soap which is red, has a fragrant odor and when used does not cause roughness in the hand.